GEDUNG SATE SEBAGAI SUMBER BELAJAR MAHASISWA PENDIDIKAN SEJARAH - M. Rizky Ramadhan; Ridho Putra Sikumbang; Azra Azril Saputra; Blasisus Franco Boy Haloho (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This article aims to examine the potential of Gedung Sate as an authentic, varied and meaningful learning resource for history education students. The method used is a Systematic Literature Review (SLR) with a descriptive qualitative approach, analyzing 15 selected articles from 100 articles obtained through the Sinta, Scopus and Google Scholar databases for the years 2000–2026. The analysis was carried out using a thematic approach which focused on three main themes, namely historical value, architectural value and the potential of Gedung Sate as a learning resource. The results of the study show that Gedung Sate has significant historical value as a silent witness to Dutch East Indies colonialism and the struggle for Indonesian independence, unique architectural value as a blend of the Indo-European Stijl style between European and Asian traditions, as well as great educational potential through various learning models such as field visits, primary source analysis, and interviews. Since transforming into a museum, Gedung Sate has increasingly opened up space for innovative and contextual history learning. Even though there are challenges in the form of time and cost constraints, the synergy between administrators, lecturers and students is considered capable of optimizing its use. It was concluded that Gedung Sate is worthy of being a meaningful source of local history learning in forming historical awareness and love of the homeland of history education students.